BREAKING INTO THE RESIDENTIAL PROPERTY MARKET: DEVELOPING AN EFFECTIVE 7+1P MARKETING MODEL FOR CLOSING DEALS - Tina Muhardika Handayani; Muammar Rinaldi; M. Asyari Syahab; Shintami Oktavia; Nazwa Aulia Putri Lubis (CV. Radja Publika, 2026)
The objective of this study is to analyze the contribution of an expanded marketing mix, specifically the 7+1P model (Product, Price, Place, Promotion, People, Process, Physical Evidence, and Privacy), to the success of closing deals in subsidized housing in Medan City. The research utilizes a quantitative approach with descriptive and verification designs, involving a sample of 350 respondents including buyers, developers, and marketing personnel. Data were collected via closed questionnaires and analyzed through multiple linear regression using SPSS software. The results demonstrate that all elements of the 7+1P marketing mix Product, Price, Place, Promotion, People, Process, Physical Evidence, and Privacy have a positive and significant effect on closing deals both partially and simultaneously. The model explains 68% of the variation in closing success, with Privacy emerging as the most influential factor, followed by Product and Place. Consequently, it is recommended that developers strategically integrate privacy elements, such as personal data protection, digital transaction security, and residential environmental comfort, as key differentiators to build consumer trust. Furthermore, developers must continue to optimize product quality and strategic locations to remain competitive and meet the specific housing needs of low-income communities.